Inhibition of amyloid beta fibril formation by monomeric human transthyretin. (14th March 2018) - Garai, Kanchan; Posey, Ammon E.; Li, Xinyi; Buxbaum, Joel N.; Pappu, Rohit V.
Abstract: Transthyretin (TTR) is a homotetrameric protein that is found in the plasma and cerebrospinal fluid. Dissociation of TTR tetramers sets off a downhill cascade of amyloid formation through polymerization of monomeric TTR. Interestingly, TTR has an additional, biologically relevant activity, which pertains to its ability to slow the progression of amyloid beta (Aβ) associated pathology in transgenic mice. In vitro, both TTR and a kinetically stable variant of monomeric TTR (M‐TTR) inhibit the fibril formation of Aβ1‐40/42 molecules. Published evidence suggests that tetrameric TTR binds preferentially to Aβ monomers, thus destabilizing fibril formation by depleting the pool of Aβ monomers from aggregating mixtures. Here, we investigate the effects of M‐TTR on the in vitro aggregation of Aβ1‐42 . Our data confirm previous observations that fibril formation of Aβ is suppressed in the presence of sub‐stoichiometric amounts of M‐TTR. Despite this, we find that sub‐stoichiometric levels of M‐TTR are not bona fide inhibitors of aggregation. Instead, they co‐aggregate with Aβ to promote the formation of large, micron‐scale insoluble, non‐fibrillar amorphous deposits. Based on fluorescence correlation spectroscopy measurements, we find that M‐TTR does not interact with monomeric Aβ. Two‐color coincidence analysis of the fluorescence bursts of Aβ and M‐TTR labeled with different fluorophores shows that M‐TTR co‐assembles with soluble Aβ aggregates and this appears to drive the co‐aggregation into amorphous precipitates. Our results suggest that mimicking the co‐aggregation activity with protein‐based therapeutics might be a worthwhile strategy for rerouting amyloid beta peptides into inert, insoluble, and amorphous deposits.